Cultural Cleansing and Mass Atrocities - Weiss, Thomas G. (Getty Publications, 2020)
Cultural Cleansing and Mass Atrocities: Protecting Cultural Heritage in Armed Conflict Zones addresses the connection between cultural heritage and cultural cleansing, mass atrocities, and the destruction of cultural heritage. Pulling together various threads of discourse and research, Cultural Cleansing and Mass Atrocities outlines the issues, challenges, and options effecting change.